The clinical characteristics, mechanism and management of immune checkpoint inhibitor-related arthritis - Gao, Jian; Miao, Jinlin; Chen, Zhinan; Zhu, Ping (Frontiers in Immunology, 2026)
BackgroundImmune-related adverse events, notably arthritis (irAE-arthritis), frequently occur in patients receiving immune checkpoint inhibitors. Arthritis severity varies from mild to severe, adversely impacting quality of life. Despite reports in clinical trials and real-world studies, the pathophysiology and optimal management of irAE-associated arthritis (irAE-arthritis) are still unclear.MethodsFrom the inception to September 25, 2025, a search was conducted on PubMed, EMBASE, and MEDLINE for case reports/series on irAE-arthritis.FindingsThe most common rheumatic irAEs were arthritis. Various rheumatic syndromes have been reported, such as arthralgia, mono-/oligo-/polyarthritis, reactive and psoriatic arthritis, RS3PE, tenosynovitis. The onset of irAE-arthritis is attributed to T cell dysregulation, B cell activation with autoantibody production, cytokine - mediated inflammation, and impaired immune tolerance due to Treg dysfunction. NSAIDs, intra-articular/systemic corticosteroids, csDMARDs, and biologics play key roles in irAE-arthritis management, and JAK inhibitors may emerge as a significant therapeutic strategy in the future.ConclusionGiven the increasing use of immunotherapy in oncology and other fields, developing a comprehensive understanding of irAE-arthritis is crucial. This review aims to provide an in-depth overview of current knowledge on irAE-arthritis, including its epidemiology, clinical presentation, underlying mechanisms, and management approaches.